Situation and solutions for development of the ceramic industry in Binh Duong until 2030 - Pham, Trần Quang Hưng; Tran, Thị Thùy Trang (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
Coming to the ceramic industry in Binh Duong, we will step by step witness the talented hands of artisans with many extremely valuable and exquisite ceramic products. However, the ceramic industry in Binh Duong has not yet developed commensurate with its potential due to different reasons. The article will focus on using qualitative research methods, whereby the authors analyze documents and use statistics to assess the current situation ceramic industry activities in Binh Duong province, thereby highlighting limitations and explaining the causes of existing difficulties. Finally, the authors propose solutions to develop human resources, improve competitiveness in international market, and improve science and technology to create high quality-products, various designs in order to preserve traditional cultural values, develop socio-economic, create employment opportunities and increase income for local people.